Risk factors for gastric cancer: A comprehensive analysis of observational studies - Hui, Yuqing; Tu, Chunyi; Liu, Danlei; Zhang, Huijie; Gong, Xiaobing (Frontiers in Public Health, 2023)
Background: Multifarious factors have a causal relationship with gastric cancer (GC) development. We conducted an umbrella review to evaluate the strength of the evidence examining nongenetic risk factors for gastric cancer. Methods: PubMed, Web of Science, and the Cochrane Library were searched from inception to November 10, 2021 to identify meta-analyses of observational studies examining the association between environmental factors and GC risk. For each meta-analysis, the random effect size, 95% confidence interval, heterogeneity among studies, and evidence of publication bias were assessed; moreover, the evidence was graded using predefined criteria, and the methodological quality was evaluated using AMSTAR 2. Results: A total of 137 associations were examined in 76 articles. Among these meta-analyses, 93 associations yielded significant estimates (p < 0.05). Only 10 associations had strong epidemiologic evidence, including 2 risk factors (waist circumference and bacon), and 8 protective factors (dietary total antioxidant capacity, vegetable fat, cruciferous vegetable, cabbage, total vitamin, vitamin A, vitamin C, and years of fertility); 26 associations had moderate quality of evidence; and the remaining 57 associations were rated as weak. Ninety-four (68.61%) associations showed significant heterogeneity. Twenty-five (18.25%) associations demonstrated publication bias. Conclusions: In this umbrella review, multiple associations were found between environmental factors and GC with varying levels of evidence. Healthy dietary habits and lifestyle patterns could reduce the risk for GC. However, further high-quality prospective studies are still necessary to draw more definitive conclusions.